Prognostic and diagnostic potential of miR-146a in oesophageal squamous cell carcinoma - Wang, Cong (Br J Cancer, 2016)
BACKGROUND: Accumulating evidence indicates that dysregulated microRNA-146a (miR-146a) is involved in tumour genesis and cancer progression. We aimed to evaluate its expression level and the potential for the diagnosis and prognosis in oesophageal squamous cell cancer (ESCC). METHODS: We examined miR-146a expression in 62 pairs of ESCC cancerous and matched paracancerous tissue, 115 formalin-fixed paraffin-embedded (FFPE) tissue samples and serum samples from 154 ESCC patients and 154 healthy volunteers using quantitative reverse transcription–PCR (qRT–PCR). Kaplan–Meier method, Cox regression and receiver-operating characteristic (ROC) curve analysis were applied to analyse its prognostic and diagnostic value. RESULTS: MicroRNA-146a expression level was significantly decreased in ESCC tissue compared with paracancerous tissue (P<0.001). Its regulation level was negatively associated with T factor and TNM stage. Kaplan–Meier curve revealed that its downregulation level predicted worse overall survival (OS) and progression-free survival (PFS). Both univariate and multivariate analyses identified miR-146a expression as independent prognostic factor for OS and PFS. Serum miR-146a was significantly reduced in ESCC patients than in healthy controls (P<0.001). Area under the curve ROC value, sensitivity and specificity for this marker were 0.863±0.033, 85.7% and 68.6% in the Discovery Group, and 0.891±0.027, 82.1% and 83.3% in the Validation Group. CONCLUSIONS: MicroRNA-146a is significantly reduced in cancerous tissue and serum samples of ESCC patients. It is an ideal biomarker for the prognosis and diagnosis of ESCC.